Formation for public life: Bonhoeffer's approach to theological education. Issue 2 (14th April 2020) - Norris, Kristopher
Abstract: This essay addresses the role of theological education in shaping how Christian leaders and institutions respond to public debate, conflict, and crisis by analyzing Bonhoeffer's approach to theological education in times of conflict and crisis. It argues that his pedagogical approach of education as formation for public life should inform our pedagogical practice, as the church increasingly engages in a diverse pluralistic public and political life.